In vitro activity of imipenem/relebactam against Pseudomonas aeruginosa isolates recovered from ICU patients in Spain and Portugal (SUPERIOR and STEP studies). (5th September 2022) - Hernández-García, Marta; García-Castillo, María; Melo-Cristino, José; Pinto, Margarida F; Gonçalves, Elsa; Alves, Valquíria; Vieira, Ana Raquel; Ramalheira, Elmano; Sancho, Luísa; Diogo, José; Ferreira, Rui; Cruz, Hugo; et al.
Abstract: Objectives: To study the in vitro activity of imipenem/relebactam and comparators and the imipenem/relebactam resistance mechanisms in a Pseudomonas aeruginosa collection from Portugal (STEP, 2017–18) and Spain (SUPERIOR, 2016–17) surveillance studies. Methods: P. aeruginosa isolates ( n  = 474) were prospectively recovered from complicated urinary tract (cUTI), complicated intra-abdominal (cIAI) and lower respiratory tract (LRTI) infections in 11 Portuguese and 8 Spanish ICUs. MICs were determined (ISO broth microdilution). All imipenem/relebactam-resistant P. aeruginosa isolates ( n  = 30) and a subset of imipenem/relebactam-susceptible strains ( n  = 32) were characterized by WGS. Results: Imipenem/relebactam (93.7% susceptible), ceftazidime/avibactam (93.5% susceptible) and ceftolozane/tazobactam (93.2% susceptible) displayed comparable activity. The imipenem/relebactam resistance rate was 6.3% (Portugal 5.8%; Spain 8.9%). Relebactam restored imipenem susceptibility to 76.9% (103/134) of imipenem-resistant isolates, including MDR (82.1%; 32/39), XDR (68.8%; 53/77) and difficult-to-treat (DTR) isolates (67.2%; 45/67). Among sequenced strains, differences in population structure were detected depending on the country: clonal complex (CC)175 and CC309 in Spain and CC235, CC244, CC348 and CC253 in Portugal. Different carbapenemase gene distributions were also found: VIM-20 ( n  = 3), VIM-1 ( n  = 2), VIM-2 ( n  = 1) and VIM-36 ( n  = 1) in Spain and GES-13 ( n  = 13), VIM-2 ( n  = 3) and KPC-3 ( n  = 2) in Portugal. GES-13-CC235 ( n  = 13) and VIM type-CC175 ( n  = 5) associations were predominant in Portugal and Spain, respectively. Imipenem/relebactam showed activity against KPC-3 strains (2/2), but was inactive against all GES-13 producers and most of the VIM producers (8/10). Mutations in genes affecting porin inactivation, efflux pump overexpression and LPS modification might also be involved in imipenem/relebactam resistance. Conclusions: Microbiological results reinforce imipenem/relebactam as a potential option to treat cUTI, cIAI and LRTI caused by MDR/XDR P. aeruginosa isolates, except for GES-13 and VIM producers.